Pemanfaatan Ekstrak Wolffia untuk Pembuatan Masker Gel Peel-Off sebagai Perawatan Kulit Wajah - Helvina, Puteri; Ridwan, Ridwan; Elwina, Elwina (Politeknik Negeri Lhokseumawe, 2024)
Wolffia is one of the smallest plants in the world that has a very high content of protein and antioxidants. Protein has good benefits for producing and replacing dead body cells so that it is able to maintain healthy skin. Skin that is continuously exposed to free radicals can cause damage to the function of body cells. Prevention and protection suitable for warding off these free radicals is by using a peel off gel face mask and containing good antioxidant activity. The purpose of this study is to obtain the physical quality of the best peel-off gel mask preparations of wolffia extract and products. The research was carried out using the experimental design method by varying wolffia extract concentrations of 6%; 6.5%; 7%; 7.5%; 7.5%; and 8% with polyvinyl alcohol (PVA) concentrations of 12%; 12.5%; 13%; 13.5%; and 14%. Gel mask peel off wolffia extract organoleptic smells typical of wolffia plants, gel-shaped and deep green in color. The best product from the results of this study is found in the 21st product with a concentration of 8% wolffia and 14% polyvinyl alcohol. This product has a pH of 6 with a dry time at 05:44 minutes. Based on the IC50 value, the Antioxidant Activity obtained in the wolffia extract peel-off gel mask product is 6.837 μg/mL and is categorized in the classification of very strong antioxidant activity.